Verbal communication competencies for first-year primary learners and their relationship to phonemic awareness. (Linguistic field study) - Larabi, Tarek; Rachid, Halim (Journal of Human Sciences, 2021)
Many of the problems of teaching Arabic, in particular, are due to phonemic awareness and its effect on the communication process of learners. The study aimed to identify the effect of training on phonemic awareness skills among first-year primary school learners on developing their verbal communicative competencies, by focusing on three important linguistic purposes: Concepts of communicative competencies.Verbal communication competencies- The field study: demonstrating phonemic awareness skills of first-year elementary learners. The study aims to identify learners with linguistic sounds, control their regularity in the different places of words and their ability to connect between spoken and written, that is, between phonemic pieces and syllables and their written drawing, and their ability to link the total number of component pieces For one word, separating the pieces in the word, combining them, replacing each other ...